The effect of alterations in effective seat tube angle on cycling performance, economy and muscle recruitment - Chye, Teo Choon (Department of Human Biology, 2018)
Introduction: The bicycle seat tube angle (STA) has been used in scientific research to investigate cycling performance since the early 1980's and has led to inconclusive findings when manipulated between 69° and 82° STA configuration. Most of these studies did not clearly indicate the handlebar positioning in relation to the change in STAs. In addition, the studied duration and intensity were not a true reflection for cycling performance during races. Aim: The study aimed to compare the effect of independent alteration of effective seat tube angle (ESTA) on gross muscle activities, body kinematics and gross economy for well-trained cyclists. Methods: Ten well-trained male cyclists (mean ± SD; age 37.8 ± 3.6 years, height 178.2 ± 3.8 cm, body mass 76.9 ± 8.0 kg, VO₂ₘₐₓ 51.6 ± 5.3 ml/kg/min with 6.8 ± 2.6 years cycling experience and an average training load of 5.8 ± 2.3 hours per week for three months prior) were volunteered for this study. All cyclists were randomly assigned to either a forward or rearward saddle position after an initial preferred saddle cycling position. Each cycling position was performed at 60% of Wₚₑₐₖ for one hour with forty reflective markers placed on bony landmarks described by Vicon full body model Plug-in gait and EMG electrodes placed on the right lower limb on seven muscles. Results: The mean power output and cadences during one hour submaximal steady state cycling differed by a maximum of 0.7W and 3.5 repetitions per minute respectively between three trials. VO₂ values (P=0.95), respiratory exchange ratio (P=0.39) and heart rate (P=0.92) for the trials were not significantly different. Mean angles for each joint and gross muscle activation patterns across the three trials were not significantly different. Magnitude-based inferences statistics showed "possible beneficial effects" on knee and ankle joint kinematics when comparing the forward and rearward saddle displacement. A progressive increase in integrated EMG values was observed for gluteus maximus, biceps femoris and rectus femoris from forward to rearward position. Both vastus lateralis and vastus medialis decreased activation in forward and rearward positions as compared to preferred position. However, none of these changes were statistically significant. Conclusion: Preserving the joint kinematics of the elbow, shoulder, hip, knee and ankle joint of the cyclist when changing the saddle displacement effectively negate any change in heart rate, oxygen consumption and respiratory exchange ratio. Nonetheless, the knee and ankle joints were increased by 1° and decreased by 1.5° respectively when saddle was moved forward. Similar knee and ankle joints effects were also detected with when saddle was moved rearward, which were decreased by 3° and increased by 2° respectively. Therefore, dynamic joint angles should be controlled for future studies when manipulating saddle displacement during cycling. The seven lower limb muscles activations were not statistically significant different when using traditional statistical methods and magnitude type statistic also indicates most unlikely or very unlikely benefits for all surface EMG variables between saddle displacements. These could be due to the high degrees of variability in EMG signal during cycling. Therefore, greater numbers of participants are encouraged for future studies aimed at understanding the coordination of agonist and antagonist muscles at different ESTA. Key words: Effective seat tube angle, submaximal cycling, 3D joint kinematics, electromyography (EMG).